Managing the One-Person Library - Cooperman, Larry (Chandos Information Professional Series, 2014)
Managing the one-person library provides a useful and needed resource for solo librarians confronted with the challenges of running a small library. The author uniquely focuses on topics encountered by solo librarians, such as IT troubleshooting and library security. Chapters on library management, collection development, serials management, and library marketing are included to enable solo librarians to easily manage day-to-day operations in these areas, and advise on how to respond to any challenges that should (and will) arise. This book will provide a much-needed resource manual that will allow solo librarians of all backgrounds, and paraprofessionals, to manage their collections as effectively as their larger librarian counterparts.Written by a librarian with extensive solo library management in the fieldTargeted to all types of solo librarians (e.g., medical, law, academic)Essential reading for paraprofessional librarians who manage one-person libraries